Optimization and analysis of permanent magnet assisted reluctance generator with interior rare - Earth - Less combined magnetic poles for extended range electric vehicles - Zeng, Xianjun; Tao, Bingquan; Sun, Xiuqian; Ma, Jianwei (Frontiers in Mechanical Engineering, 2025)
To address the issues of large cogging torque and poor sinusoidal waveform of induced electromotive force in traditional pure rare earth permanent magnet generators for extended-range electric vehicles, a novel permanent magnet-assisted reluctance generator with hybrid magnetic poles formed by rare-earth and non-rare-earth permanent magnets for series excitation is proposed. The topological structure and operating principle of the generator are introduced. Based on this, an equivalent magnetic circuit model is established, and the analytical expressions of the cogging torque and induced electromotive force of the permanent magnet generator are derived to analyze their main influencing factors. A finite element model of a three-phase 8-pole 36-slot interior dual radial combined magnetic pole permanent magnet generator is established. Sensitivity hierarchical optimization is carried out on the relevant parameters such as the size and position angle of the combined magnetic poles and their corresponding magnetic barriers, so as to obtain the structural parameters affecting the generator’s cogging torque, the amplitude of the induced electromotive force, and the total harmonic distortion (THD) of the induced electromotive force waveform. Then, the data is normalized and a weighted evaluation index is used to obtain the optimal solution combination. Finally, the feasibility of this method is verified through finite element simulation analysis. The results indicate that the amplitude of the no-load induced electromotive force of the generator increased by 6.97%, the THD decreased by 16.2%, and the cogging torque was weakened by 43.8%, effectively improving the output performance of the generator.